The urban motorcycle taxi sector in Sub-Saharan Africa: needs, practices and equity issues - Fredrick Owino; Krijn Peters; Jack Jenkins; Paul Opiyo; Reginald Chetto; Simon Ntramah; Mugisha Marion Mutabazi; James Vincent; Ted P. Johnson; Rosemarie T. Santos; Patrick Hayombe (Urban, Planning and Transport Research)
Motorcycle taxis in Sub-Saharan Africa are an essential component of the urban transport mix, providing vital services - such as access to markets, education and health facilities - to city dwellers across the continent. Transport regulators and policymakers have nonetheless remained reluctant to engage with this expanding sector, which seems to be the preferred mode of transport. Primary data were collected in five Sub-Saharan African countries during the last quarter of 2020 using qualitative interviews with key stakeholders relevant to the urban motorcycle taxi sector and quantitative motorcycle taxi operator surveys. There is a substantial prospect to come up with best practices within this sector by identifying and learning from the experiences of various stakeholders including motorcycle taxi and motor tricycle taxi operators, unions, institutions, traffic police, and users of these services. In addition, the data shows that there are ample opportunities for increased collaboration between the stakeholders, to ensure the sector’s continuous contribution to socio-economic development. Planning for a more sustainable and integrated transport system in Sub-Saharan African cities requires acknowledging the significant position taken up in this by the motorcycle and tricycle taxi.